Characterization of phytoconstituents and potential bioactivity of Annona reticulata L. leaf extract - Shahriar, Mohammad; Khair, Nishat Zareen; Sheikh, Zara; Chowdhury, Sayeeda Fahmee; Kamruzzaman, Md.; Bakhtiar, Md. Shawkatul Islam; Chisty, Sharmin Jahan (© 2016 Journal of Pharmacognosy and Phytochemistry, 2016)
This article was published in the Journal of Pharmacognosy and Phytochemistry [©2016 Journal of Pharmacognosy and Phytochemistry]